Correlation Between MERI and Hearing After Tympanoplasty - Sharma, Anshu; Saxena, R. K.; Verma, Lok Ram; Bhandari, Shama (Journal of Nepalgunj Medical College, 2017)
Background: Chronic otitis media is otological challenge in the developing countries it is particularly single most common cause of hearing impairement.Objective: The objective of this study was to observe the impact of prognostic factor middle ear risk index on hearing of patients undergoing tympanoplasty for chronic otitis media.Methods: This was a prospective analytical study conducted in 50 patients planned for tympanoplasty for chronic otitis media and evaluation done by MERI (Middle Ear Risk Index) and pure tone audiometry.Results: This study shows that most of the patients had mild MERI (64%), followed by severe MERI (20%) and then moderate MERI (16%). The mean preoperative PTA average was 44.34 dB (SD 8.01 dB) for patient with mild MERI, 44.75 dB (SD 5.87 dB) for patient with moderate MERI, and 54.9 dB (SD 14.05 dB) for patient with severe MERI and the mean preoperative A-B gap was 37.36 dB (SD 5.73 dB). Post operatively for mild MERI mean hearing gain is 12-14dB, for moderate MERI mean hearing gain is 10-13dB and for severe MERI mean hearing gain is 10-13dB and post operative mean A-B gap was improved by 10-11dB. There is a statistically significant hearing improvement in A-B gap with different types of MERI.Conclusion: MERI scoring is useful for predicating the outcome of hearing after tympanoplasty.JNGMC Vol. 13 No. 2 December 2015, Page: 6-9